Changes in the coffee grain color related to the post-harvest operations - Abreu, Giselle Figueiredo; Pereira, Cristiane Carvalho; Malta, Marcelo Ribeiro; Clemente, Aline Consolação Sampaio; Coelho, Luis Filipe Serafim; Rosa, Sttela DVF (Coffee Science - ISSN 1984-3909, 2015)
The color evaluation of coffee grains becomes important as atypically colored coffee or different levels of whiteness will receive lower price on the market. In addition to commercial impairment, changes in color are indicative of the occurrence of oxidative processes and biochemical damage, which can alter the flavor and aroma precursors of the grains, resulting in lower beverage quality. Thus, the aim of this study is to evaluate the color characteristics in coffee grains with different levels of quality that were processed, benefited and stored under different conditions. Coffee fruits were harvested in the cherry stage and dry processed and wet processed. Grains were dried until reaching 11% moisture content and subjected to three treatments (manual hulling, mechanical hulling and without hulling), and were stored under two conditions (10ºC and 50% RU; and 25ºC without relative humidity control). After eight months of storing, the color parameters of the grains, the physiological and sensory quality were evaluated. The intensity of the green and blue colors and the brightness of the grains are affected by the processing and hulling methods, and storage conditions. The wet processed coffee grains have a more intense greenish color compared to the dry processed ones. Coffee grains stored under lower temperature have lower brightness indexes and “b” color parameter, as well better physiological quality.